Association Between Student Loan Debt on Graduation, Demographic Characteristics and Initial Choice of Practice Setting of Pharmacists - Akeem A. Yusuf, B.Pharm; Jon C. Schommer, PhD; David A. Mott, PhD; William R. Doucette, PhD; Caroline A. Gaither, PhD; David H. Kreling, PhD (INNOVATIONS in Pharmacy, 2011)
Objectives: (1) To examine trends in level of student loan indebtedness for groups of pharmacists that were first licensed between 1980 and 2006; (2) To examine if demographic variables are associated with level of student loan indebtedness; (3) To examine the association between student loan debt and choice of practice setting while controlling for demographic variables.Methods: Data for this study were collected from a national random sample of 3,000 pharmacists using a self administered survey. Descriptive statistics were used to examine trends in level of indebtedness. The relationships between level of indebtedness, demographic variables and practice setting choice were examined using Chi-square statistics. Multinomial logistic regression was used to determine the independent association of student loan debt and choice of practice setting while controlling for demographic variables.Results: The proportion of licensed pharmacists reporting student loan debt after graduation, and the mean amount of debt incurred increased between 1980 and 2006. Non-white pharmacists incurred debt at a higher proportion compared to white, and they also incurred significantly higher levels of debt. A lower level of indebtedness was associated with choosing independent practice over chain practice.Conclusions: Student loan indebtedness has been increasing over time, especially for non-white pharmacy students. Future research should be done to examine other factors that might influence student debt load, work contributions and choice of practice settings. The affordability of pharmacy education for students of color and how salaries may or may not help off-set these costs also should be examined closely.